THE INFLUENCE OF PRINCIPAL LEADERSHIP, ORGANIZATIONAL CULTURE, AND EMOTIONAL INTELLIGENCE THROUGH JOB SATISFACTION ON THE PERFORMANCE OF PUBLIC HIGH SCHOOL TEACHERS IN SAMALANGA DISTRICT, BIREUEN REGENCY - Nazaruddin, Nazaruddin; Zainuddin (LPPM-UNIKI, 2020)
This study aims to examine the factors that influence teacher performance